Enhancing learning in small businesses. (11th March 2022) - Coetzer, Alan; Redmond, Janice; Sharafizad, Jalleh; Lundy, Judy
Abstract: This study addresses knowledge gaps relating to how small business owner/managers facilitate employee learning and how distinctive characteristics of small businesses affect employee learning. Data were collected through interviews with owner/managers and employees and observation of conditions in the physical, social, and organisational environments that might help or hinder informal learning. The findings provide a situated, context‐sensitive, and triangulated account relating to two research questions. We find that owner/manager physical and social proximity to employees is a key facilitating factor. Proximity creates the potential for owner/managers to facilitate learning through modelling, provision of immediate feedback and guidance. The owner/manager's positive influence on learning stemming from their physical and social proximity to employees is accentuated by owner/managers employing management styles facilitative of learning. Our findings suggest that a "family‐like" culture and the social cohesion in the businesses had enabling effects on employee participants' informal learning, while their lack of opportunities for formal learning would have inhibiting effects.